2011
DOI: 10.1111/j.1365-2915.2011.00950.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature induces trade-offs between development and starvation resistance in Aedes aegypti (L.) larvae

Abstract: While heightened temperature increases the development rate of mosquitoes, for Aedes aegypti, larvae that commonly experience food limitation in urban habitats, temperature effects on adult production may also be influenced by changes in the capacity of larvae to survive without food. We carried out experiments at 2°C intervals between 20 and 30°C on the growth, maturation rate and the longevity of optimally fed larvae placed in starvation. Overall, both growth rate and starvation resistance were lower in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…Details of preparation are previously described (Padmanabha et al 2011). To simulate a range of food conditions that Ae.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of preparation are previously described (Padmanabha et al 2011). To simulate a range of food conditions that Ae.…”
Section: Methodsmentioning
confidence: 99%
“…For example, we recently showed that heightened development rate at increased temperatures can increase the mortality rate of early-instar Ae. aegypti (Padmanabha et al 2011). Because larval mortality as a result of resource competition is known to play a major role in the regulation of adult Ae.…”
mentioning
confidence: 99%
“…This change could have an impact on morphological traits of mosquitoes. 61,62 Wing centroid sizes of females from this sampling period were larger (2.92 versus 2.81 mm) than field females sampled in the warmer months (t = 2.25, df = 151, P = 0.03). There was, however, no evidence of a difference in thorax length (t = 0.98, df = 160, P = 0.33).…”
Section: Size and Shape In Released Mosquitoesmentioning
confidence: 99%
“…Previous studies have shown that the temperature optimum for Ae. aegypti larval and pupal development, with short development times and high survival rates, is in the range of 24°–34°C (Bar-Zeev 1958; Rueda et al 1990; Tun-Lin et al 2000; Kamimura et al 2002; Mohammed and Chadee 2011; Padmanabha et al 2011b; Richardson et al 2011; Farjana et al 2012; Eisen et al 2014). We found that model-projected water temperatures from May to September 2011 in a representative container (gray, medium-sized bucket located in half shade) consistently exceeded 24°C in Veracruz City and commonly exceeded 24°C in Rio Blanco but very rarely did so in Puebla City (Figure 11).…”
Section: Discussionmentioning
confidence: 99%